Alkyne Metathesis with Silica‐Supported and Molecular Catalysts at Parts‐per‐Million Loadings. Issue 45 (3rd August 2016) - Estes, Deven P.; Bittner, Celine; Àrias, Òscar; Casey, Martin; Fedorov, Alexey; Tamm, Matthias; Copéret, Christophe
Abstract: Improvement of the activity, stability, and chemoselectivity of alkyne‐metathesis catalysts is necessary before this promising methodology can become a routine method to construct C≡C triple bonds. Herein, we show that grafting of the known molecular catalyst [MesC≡Mo(O t BuF6 )3 ] (1, Mes=2, 4, 6‐trimethylphenyl, O t BuF6 =hexafluoro‐ tert ‐butoxy) onto partially dehydroxylated silica gave a well‐defined silica‐supported active alkyne‐metathesis catalyst [(≡SiO)Mo(≡CMes)(O t BuF6 )2 ] (1 /SiO2‐700 ). Both1 and1 /SiO2‐700 showed very high activity, selectivity, and stability in the self‐metathesis of a variety of carefully purified alkynes, even at parts‐per‐million catalyst loadings. Remarkably, the lower turnover frequencies observed for1 /SiO2‐700 by comparison to1 do not prevent the achievement of high turnover numbers. We attribute the lower reactivity of1 /SiO2‐700 to the rigidity of the surface Mo species owing to the strong interaction of the metal site with the silica surface. Abstract : Up to speed : Extremely low catalyst loadings and turnover numbers as high as 54 000 were possible with the new heterogeneous alkyne‐metathesis catalyst [(≡SiO)Mo(≡CMes)(O t BuF6 )2 ], as well as turnover numbers up to 185 000 with its molecular precursor [MesC≡Mo(O t BuF6 )3 ] (see picture; O t BuF6 =hexafluoro‐ tert ‐butoxy). High reactivity, selectivity, and stability of the catalysts were observed with carefully purified alkynes.